Computer and computing technologies in agriculture XI : 11th IFIP WG 5.14 International Conference, CCTA 2017, Jilin, China, August 12-15, 2017, Proceedings.: 11th IFIP WG 5.14 International Conference, CCTA 2017, Jilin, China, August 12-15, 2017, Proceedings. Part I (2019) - Unknown
No abstract available